Social factors of development the psychological boundaries of vital functions of the adoptive family - Tatyana Melnichuk (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
The article describes the main characteristics of functioning the adopted family as a small group that develops by the analogy of family of the blood based on the preservation the psychological boundaries of the family, its integration into the nearest social environment and its integrity even after the children reach the age of majority. On the ground of theoretical and practical analysis, own social experience analysed comparing Ukrainian and international experience in the implementation of socio-psychological work with adoptive parents and their families.